2022
DOI: 10.1088/1402-4896/ac9ba1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ge addition on the structure, mechanical and magnetic properties of (CoCrFeNi)100-xGex high-entropy alloys

Abstract: Alloying non-metallic elements can not only change the structure of alloys, but also tailor the mechanical and physical properties. The microstructure, mechanical and magnetic properties of (CoCrFeNi)100-xGex (molar ratio, x = 0 ~ 33) high-entropy alloys (HEAs) have been systematically studied in this paper. The experiment results show that the (CoCrFeNi)100-xGex HEAs transform from a face-centered cubic (FCC) to a body-centered cubic (BCC) solid solution when 10 ≤ x ≤ 25, and a hexagonal intermetallic compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…The refractory multi-principal element alloys (RMPEAs) have many advantages over traditional alloys [1], such as high strength and stability at high temperatures [2][3][4][5][6], which can be utilized to gas turbine engines in the aerospace industry [7][8][9][10][11]. In the past years, multi-principal element alloys (MPEAs) are traditionally assumed to be random solid solutions [12].…”
Section: Introductionmentioning
confidence: 99%
“…The refractory multi-principal element alloys (RMPEAs) have many advantages over traditional alloys [1], such as high strength and stability at high temperatures [2][3][4][5][6], which can be utilized to gas turbine engines in the aerospace industry [7][8][9][10][11]. In the past years, multi-principal element alloys (MPEAs) are traditionally assumed to be random solid solutions [12].…”
Section: Introductionmentioning
confidence: 99%
“…3 The special structure of HEAs with its excellent comprehensive properties, such as high hardness, excellent magnetic properties, outstanding oxidation resistance, superior corrosion resistance, and excellent wear resistance has a broad application prospect. [4][5][6][7][8] Although traditional soft magnetic alloys have excellent magnetic properties, there are some problems such as low strength and poor corrosion resistance. Studies have shown that HEAs are an ideal soft magnetic material with excellent soft magnetic properties and excellent mechanical properties.…”
mentioning
confidence: 99%